1996
DOI: 10.1164/ajrccm.153.1.8542104
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-sparing effect of azelastine in the management of bronchial asthma.

Abstract: The objective of this double-blind trial was to evaluate the corticosteroid-sparing effect of azelastine in patients with chronic bronchial asthma. A total of 193 subjects received either 6 mg of azelastine twice per day or placebo (in a 2:1 ratio) in combination with beclomethasone dipropionate (6 to 16 inhalations per day). The number of daily inhalations of the corticosteroid was reduced until maximum reduction or elimination was achieved. Patients then entered a 12-wk maintenance period, during which patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Information on major study characteristics of the 19 studies retrieved for our meta-analysis is presented in table 2. All degrees of asthma severity were present, from pollen-induced asthma [21,31,36] to steroid-sparing studies (oral corticosteroids [27]; inhaled corticosteroids [23]). Asthma was usually defined by a history of reversible airflow obstruction, with impaired lung function that improved considerably after use of inhaled bronchodilators.…”
Section: Resultsmentioning
confidence: 99%
“…Information on major study characteristics of the 19 studies retrieved for our meta-analysis is presented in table 2. All degrees of asthma severity were present, from pollen-induced asthma [21,31,36] to steroid-sparing studies (oral corticosteroids [27]; inhaled corticosteroids [23]). Asthma was usually defined by a history of reversible airflow obstruction, with impaired lung function that improved considerably after use of inhaled bronchodilators.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, H 1 R blocker azelastine reduced the frequency of administration of inhaled corticosteroids without loss of pulmonary function in a clinical trial with patients with chronic asthma (Busse et al, 1996).…”
Section: Histaminergic Regulation Of the Signaling Of Other Receptorsmentioning
confidence: 98%
“…Drugs administered by the oral route may have an effect on both nasal and bronchial symptoms (2027). Oral H 1 -antihistamines represent the first-line treatment of allergic rhinitis but although studies have found some effect on asthma symptoms (1942,(2028)(2029)(2030), many negative studies are unpublished and pulmonary function tests are unchanged. These drugs are not recommended for the treatment of asthma (2031,2032).…”
Section: Therapeutic Consequencesmentioning
confidence: 99%